MANAJEMEN PENGEMBANGAN PENDIDIKAN KECAKAPAN HIDUP BAGI ANAK BERKEBUTUHAN KHUSUS DENGAN RETARDASI MENTAL DI SLB - Mursiawati, Mursiawati; Sukmawati, Sukmawati; Chiar, M (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study is 1) Educational development planning Life skills 2) Steps in lifeskills education service 3) Evaluation of life skills education services 4) Supporting, matters in the implementation of life skills education services 5) Efforts to overcome obstacles in implementing life skills education services. This research uses a qualitativeapproach, carried out in SLB-C Dharma Asih Pontianak with the subject of the Principal, the informants are curriculum waka, teachers and students. The study was conducted from January to March 2019. Data sources used were documentation, observation and interviews. The data validity technique uses triangulation techniques, namely: source triangulation, method triangulation, investigator triangulation, and theory triangulation. The collection technique uses primary and secondary data. The results of the study are:1) Management of developing life skills education for life skills for children with special needs with mental retardation in Dharama Asih Pontianak SLB-C. namely managementConducted in SLB has been carried out, from planning, implementation, supervision to evaluation Skill teachers have the responsibility of each, towards their students, but thereare some things that are lacking in delivery so that education is confused about the existing planning, because it directly submits to the respective skill units. Its development and preparation are carried out in accordance with teaching and learning activities left to educators and teacher skills. In the implementation is less than the maximum due to the factor of children not going to school, as well as supervision and evaluation of the skills of each teacher each unit is less effective 2) Obstacles in the implementation of life skills education services for children with special needs with mental retardation in SLB namely: lack of coordination with teachers in the field of study about the expected plan, the factors of students who are easily tired, tired, easily offended so they do not want to participate in teaching and learning activities 3) solutions to learning methods vary in providing life skills education services for children with special needs with basic skills in the field of entrepreneurship, for example: making eggs salted from the manufacturing process to themarketing of students trained and fostered, by classroom teachers and skill teachers who have junior-high and LB-high education, the level of disability is mild retardation that is able to educate and be able to train. Students are fostered, trained with smooth communication and given rewards to students, so that the learning process is comfortable and enjoyable. Keywords: Management, Life Skills, Children With Special Needs